1997
DOI: 10.1037/0033-295x.104.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Language production and serial order: A functional analysis and a model.

Abstract: In speech production, previously spoken and upcoming words can impinge on the word currently being said, resulting in perseverations (e.g., "beef needle soup" ) and anticipations (e.g., "cuff of coffee" ). These errors reveal the extent to which the language-production system is focused on the past, the present, and the future and therefore are informative about how the system deals with serial order. This article offers a functional analysis of serial order in language and develops a general formal model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
407
3
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(445 citation statements)
references
References 100 publications
(191 reference statements)
32
407
3
3
Order By: Relevance
“…Research in aphasic patients as well as computational modeling efforts have shown that as the production system breaks down more (i.e., as more errors are produced), the patterns of speech errors begin to depart from normal patterns (see Dell, Schwartz, Martin, Saffran, & Gagnon, 1997). More specifically, a computational model of word production has shown that information decays more quickly, phonological error patterns become more random (Dell, Burger, & Svec, 1997). In the present study, decay of the nonword stimuli being held in memory likely led to a higher error rate and to a few instance in which the syllable-position constraint and bias towards contextual substitution bias were violated.…”
Section: Discussionmentioning
confidence: 99%
“…Research in aphasic patients as well as computational modeling efforts have shown that as the production system breaks down more (i.e., as more errors are produced), the patterns of speech errors begin to depart from normal patterns (see Dell, Schwartz, Martin, Saffran, & Gagnon, 1997). More specifically, a computational model of word production has shown that information decays more quickly, phonological error patterns become more random (Dell, Burger, & Svec, 1997). In the present study, decay of the nonword stimuli being held in memory likely led to a higher error rate and to a few instance in which the syllable-position constraint and bias towards contextual substitution bias were violated.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is in agreement with the perceptual theory of self-monitoring, such that speakers have little or no access to their speech production process, and that self-monitoring is probably based on parsing one's own inner or overt speech [Levelt, 1983]. Furthermore, both behavioral and theoretical studies have shown that articulatory errors tend to be more perseveratory (e.g., "beef needle soup") than anticipatory (e.g., "cuff of coffee") when the error rate is higher [Dell et al, 1997]. Consistent with this serial-order model, the higher error rate accompanied by the DAF effect may be due to perseveratory errors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenomena are known from linguistic research. For example, Dell, Burger, and Svec (1997) found more anticipatory than preserveratory errors in practiced speech. Inhibitory mechanisms to ensure serial order were successfully modeled by Rumelhart and Norman (1982) in their seminal study on mechanisms responsible for motor control in typewriting (for a review see: Houghton & Tipper, 1996).…”
Section: Sequential Action Representation In Infancy 11mentioning
confidence: 99%